Investigations on the pyrolysis of microalgal-bacterial granular sludge: products, kinetics, and potential mechanisms - Cui, Baihui (2022)
This study investigated the pyrolysis of microalgal-bacterial granular sludge for producing bio-oil and biochar. Results showed that the bio-oil productivity of pyrolyzed MBGS reached 39.5-45.4 wt%, while 23.8-41.2% for the nitrogen-containing bio-oil at the temperature of 673-1073 K. Meanwhile the biochar with a nitrogen content of 3.7-7.0 wt% could also be produced. Moreover, the Van-Krevelen diagram revealed that produced bio-oil had a H/C ratio higher than that from agroforestry biomass, but its O/C ratio was found to be similar to those of coal and biochar. It further appeared from a mass conservation analysis that the highest bio-oil production yield was achieved at a pyrolysis temperature of 773 K, while the pyrolytic kinetics of MBGS in the temperature range studied was governed by the 3-D diffusion mechanism with the activation energy of 224.96 kJ·mol-1.